Degeneracy of the Antithrombin Binding Sequence in Heparin: 2‐O‐Sulfated Iduronic Acid Can Replace the Critical Glucuronic Acid. Issue 51 (31st July 2020) - Elli, Stefano; Stancanelli, Eduardo; Wang, Zhangjie; Petitou, Maurice; Liu, Jian; Guerrini, Marco
Abstract: Heparin binds to and activates antithrombin (AT) through a specific pentasaccharide sequence, in which a trisaccharide subsite, containing glucuronic acid (GlcA), has been considered as the initiator in the recognition of the polysaccharide by the protein. Recently it was suggested that sulfated iduronic acid (IdoA2S) could replace this "canonical" GlcA. Indeed, a heparin octasaccharidic sequence obtained by chemoenzymatic synthesis, in which GlcA is replaced with IdoA2S, has been found to similarly bind to and activate antithrombin. By using saturation‐transfer‐difference (STD) NMR, NOEs, transferred NOEs (tr‐NOEs) NMR and molecular dynamics, we show that, upon binding to AT, this IdoA2S unit develops comparable interactions with AT as GlcA. Interestingly, two IdoA2S units, both present in a 1 C4 ‐ 2 S0 equilibrium in the unbound saccharide, shift to full 2 S0 and full 1 C4 upon binding to antithrombin, providing the best illustration of the critical role of iduronic acid conformational flexibility in biological systems. Abstract : An alternative fit : Octasaccharide (OCTA) in unbound form (figure top) and in complex with antithrombin (bottom, top and side views) is presented. OCTA includes the active GlcNS, 6S‐IdoA2S ‐GlcNS, 3S, 6S‐IdoA2S‐GlcNS, 6S sequence as an alternative to the canonical GlcNAc/NS, 6S‐GlcA ‐GlcNS, 3S, 6S‐IdoA2S‐GlcNS, 6S AT‐binding pentasaccharide. 'Induced fit' conformational change of the glycosidic backbone and the two IdoA2S moieties surrounding the central 3‐ O ‐sulfo‐glucosamine are detected.